Opioid Free Anesthesia in Arthroscopic Knee Surgery: A Feasible Approach to Patient Care - Carson Gifford; Denise Vidal; Dail Kim; Austin Goff; Paul Reynolds (HCA Healthcare Journal of Medicine, 2026)
Background The opioid epidemic has prompted exploration of opioid-free anesthesia (OFA) techniques, but the optimal approach is still debated. While some OFA protocols substitute opioids with other agents, these alternatives can introduce their own risks. The objective of this study was to investigate whether eliminating intraoperative opioids without analgesic substitution in arthroscopic knee procedures affects postoperative pain control and opioid requirements. Methods We conducted a retrospective analysis of 205 patients who underwent arthroscopic knee procedures between August and November 2023. Patients were divided into 2 groups: those who received intraoperative fentanyl (25-200 mcg, n = 144) and those who received no intraoperative opioids (n = 61). Postoperative pain scores, morphine milligram equivalents (MME) administered, and antiemetic use were compared between groups using Mann-Whitney U tests with Bonferroni correction. Results No significant differences were found between groups in postoperative pain scores (U = 4594, P > .025) or postoperative opioid requirements (U = 4213, P > .025). Postoperative antiemetic use was similar between groups (7% in OFA group vs 6% in opioid group), though sample size precluded statistical analysis. Conclusion For arthroscopic knee procedures, the elimination of intraoperative opioids without substitution appears feasible, with no significant differences in postoperative pain control or opioid requirements compared with traditional opioid-inclusive anesthesia. From a clinical standpoint, this approach may offer a strategy for reducing cumulative opioid exposure without compromising patient comfort or introducing risks associated with opioid substitutes.